Differences between Portuguese and Brazilian Patients with Fibromyalgia Syndrome: Exploring the Associations across Age, Time of Diagnosis, and Fatigue-Related Symptoms - Alvarez, Marcos (2021)
The aim of the study was to explore the differences between Brazilian and Portuguese patients with fibromyalgia (FM) syndrome in their experience of fatigue, and to measure differences in the perception of fatigue as a function of age and duration of the diagnosis. In total, 209 Portuguese women aged between 21 and 75 years (M = 47.44; SD = 10.73) and 429 Brazilian women aged between 18 and 77 years (M = 46.51; SD = 9.24) were recruited to participate in the present study. Participants completed the Multidimensional Daily Diary of Fatigue-Fibromyalgia-17 items (MDF-Fibro-17), a specific tool to measure the level of five components of FM-related fatigue. Results showed greater perception of all the components of fatigue in the Brazilian sample. No significant differences were found related to age and duration of FM diagnosis. The multifaceted nature of FM and cultural differences suggests that individualized treatment programs may be necessary to reduce fatigue-related symptoms in patients with this syndrome.